Soit x∈R et soit f(x)=3cos(x+6π). En utilisant une formule d'addition, développer l'expression de f.
Correction
f(x)=3cos(x+6π)
cos(A+B)=cos(A)cos(B)−sin(A)sin(B)
Ce qui nous donne : f(x)=3(cos(x)cos(6π)−sin(x)sin(6π)) f(x)=3(cos(x)×23−sin(x)×21) f(x)=3×cos(x)×23−3×sin(x)×21 f(x)=cos(x)×2(3)2−sin(x)×23 Ainsi :
f(x)=23cos(x)−23sin(x)
Question 2
Soit x∈R et soit f(x)=2cos(x−4π). En utilisant une formule d'addition, développer l'expression de f.
Correction
f(x)=2cos(x−4π)
cos(A−B)=cos(A)cos(B)+sin(A)sin(B)
Ce qui nous donne : f(x)=2(cos(x)cos(4π)+sin(x)sin(4π)) f(x)=2(cos(x)×22+sin(x)×22) f(x)=2×cos(x)×22+2×sin(x)×22 f(x)=cos(x)×2(2)2+sin(x)×2(2)2 f(x)=cos(x)×22+sin(x)×22 Ainsi :
f(x)=cos(x)+sin(x)
Question 3
Soit x∈R et soit f(x)=2sin(3x+43π) . En utilisant une formule d'addition, développer l'expression de f.
Correction
f(x)=2sin(3x+43π)
sin(A+B)=sin(A)cos(B)+sin(B)cos(A)
Ce qui nous donne : f(x)=2(sin(3x)cos(43π)+sin(43π)cos(3x)) f(x)=2(sin(3x)×(−22)+22×cos(3x)) f(x)=2(−22sin(3x)+22cos(3x)) f(x)=2×(−22)sin(3x)+2×(22)cos(3x) f(x)=−2(2)2sin(3x)+2(2)2cos(3x) f(x)=−22sin(3x)+22cos(3x) f(x)=−sin(3x)+cos(3x) Ainsi :
f(x)=cos(3x)−sin(3x)
Question 4
Soit x∈R et soit f(x)=3sin(4x−32π) . En utilisant une formule d'addition, développer l'expression de f.
Correction
f(x)=3sin(4x−32π)
sin(A−B)=sin(A)cos(B)−sin(B)cos(A)
Ce qui nous donne : f(x)=3(sin(4x)cos(32π)−sin(32π)cos(4x)) f(x)=3(sin(4x)×(−21)−23×cos(4x)) f(x)=3(−21sin(4x)−23cos(4x)) f(x)=−23sin(4x)−2(3)2cos(4x) Ainsi :